Kompetensi Sosial (Societal Comptance) - Achmad Rizal Nurhuda; Nurul Fitria; Moch. Isa Ansori (International Forum of Researchers and Lecturers, 2023)
This writing discusses social competence. The purpose of this writing is to understand the meaning of social competence, the aspects of social competence, the elements of social competence, the characteristics and indicators of social competence, the factors that influence social competence, as well as the characteristics of teachers who possess social competence and the role of teachers' social competence in creating effective learning. In this article, there is data and information obtained during the data collection phase, which are then processed using a literature analysis method conducted in libraries, with documents, archives, and other types of documents as research materials. Additionally, this research can build and enhance an individual's social competence. There are many benefits that can be gained from having social competence, which not only affect oneself but also influence others and the surrounding environment.